2006
DOI: 10.1038/ja.2006.39
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cell Morphology and Intracellular Potassium Concentration in Candida albicans

Abstract: Previously we reported that valinomycin inhibited hyphal growth and induced growth as a chain of yeast cells under hyphal growth induction conditions in Candida albicans. To elucidate the hyphal growth inhibition by valinomycin, we examined the effect of various chemicals on the morphology and found that miconazole inhibited hyphal growth as well as valinomycin: both compounds promoted the leakage of potassium from cells. Analysis of intracellular potassium suggested that hyphal cells contain potassium at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…To our knowledge this is the first work characterizing the potassium efflux activity of an active transport system directly in C. albicans cells. In C. albicans, changes in intracellular potassium concentration are supposed to influence the development of cell morphology and virulence (Biswas et al, 2000;Watanabe et al, 2006). Our finding that CaCnh1 alkali metal cation/ H + antiporter is, in C. albicans cells, important for the potassium and rubidium tolerance and plays a role in the regulation of intracellular potassium concentration will certainly contribute to elucidating the nature not only of C. albicans high salt tolerance, but also its pathogenicity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To our knowledge this is the first work characterizing the potassium efflux activity of an active transport system directly in C. albicans cells. In C. albicans, changes in intracellular potassium concentration are supposed to influence the development of cell morphology and virulence (Biswas et al, 2000;Watanabe et al, 2006). Our finding that CaCnh1 alkali metal cation/ H + antiporter is, in C. albicans cells, important for the potassium and rubidium tolerance and plays a role in the regulation of intracellular potassium concentration will certainly contribute to elucidating the nature not only of C. albicans high salt tolerance, but also its pathogenicity.…”
Section: Discussionmentioning
confidence: 91%
“…The morphological switch of C. albicans cells from yeasts to hyphae is associated with a rise in internal pH (Stewart et al, 1988), and the intracellular concentration of K + is higher in cells growing in hyphal form in the presence of serum than in cells growing as yeasts (Watanabe et al, 2006). Although our results showed that deletion of both CNH1 alleles had no significant influence on K + content under conditions of exponential growth of yeast cells in minimal YNB medium, the effect of the absence of CaCnh1p on intracellular potassium concentration in hyphal cells has not yet been estimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell envelope of Candida is appeared to be damaged by the compounds as evident by shrinkage of cell surfaces, presence of non-polar bud scars, and receding of cytoplasm leading to lysis of cells. Increase in buds and bud scars implies that compound affect normal division process of yeasts resulting in a single cell with multiple attempt to divide but not resulting in increase in viable number of cells (Watanabe et al 2006). The deposition of vesicles on to the cell surface is an indicative of broken cells releasing cytoplasmic materials upon damage of cell wall and therefore, suggests fungicidal nature of compounds towards yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of extracellular K + leakage from the fungal cell was performed using the method of (Watanabe et al 2006) with little modifications. Briefly, Candida cells were grown in 100 mL SDB at 30°C, 120 rpm for 24 h. Cell pellets were harvested at 5000 rpm for 5 min and washed three times with sterile PB and suspended in 10 mL of PB.…”
Section: Methodsmentioning
confidence: 99%